Pengaruh Pengetahuan Ibu terhadap Perawatan Tali Pusat pada Bayi Baru Lahir - Nelil Mudarris; Gina Gina (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Improper care of the umbilical cord can lead to premature detachment and increase the risk of umbilical cord infection (neonatal tetanus). As long as the umbilical cord has not detached naturally, it needs to be properly cared for. Failure to do so can result in infection characterized by moisture, pus, and a foul odor around the umbilical cord. This review aims to determine the influence of mothers' knowledge on the care of the umbilical cord in newborns. This review aims to investigate the impact of mothers' knowledge on the care of the umbilical cord in newborns. This study utilizes a literature review method, utilizing journal articles obtained from Google Scholar, SINTA, and Garuda databases, published between 2019 and 2023, with full text available in the Indonesian language. Based on the reviewed journals, it was found that 7 journals discovered the influence of maternal knowledge on umbilical cord care in newborns, while 4 journals stated that there are still mothers who perform umbilical cord care incorrectly according to the procedure. Based on the literature review of 10 research journals, respondents' characteristics among postpartum mothers can be classified based on age, educational level, and occupation. All these factors significantly impact a mother's knowledge regarding the care of the umbilical cord in newborns, highlighting the importance of health education in enhancing maternal knowledge.